LANDSCAPE-ECONOMIC STATUS ASSESSMENT OF NATURAL LANDSCAPES: CRITERIA AND INDICATORS - Isomiddinov Ismoil (Zeta Repository, 2023)
This article covers specific aspects of the landscape-economic approach in assessing the general characteristics of landscapes, issues of developing assessment criteria.